Respuesta :
V(j + y) = 61y + 82
Vj + Vy = 61y + 82
Vy - 61y = 82 - Vj
y(V - 61) = 82 - Vj
y = (82 - Vj)/(V - 61)
Vj + Vy = 61y + 82
Vy - 61y = 82 - Vj
y(V - 61) = 82 - Vj
y = (82 - Vj)/(V - 61)
Answer:
[tex]y = \frac{82-Vj}{V-61}[/tex]
Step-by-step explanation:
Given the equation: [tex]V(j+y)= 61y+82[/tex]
Solve for y:
The distributive property says:
[tex]x \cdot (y+z) = x\cdot y+ x\cdot z[/tex]
Apply the distributive property on a given equation we have;
[tex]Vj+Vy= 61y+82[/tex]
Subtract 61y from both sides we get;
[tex]Vj+Vy-61y=82[/tex]
Subtract vj from both sides we get;
[tex]Vy-61y= 82-Vj[/tex]
or
[tex]y(V-61)= 82-Vj[/tex]
Divide both sides by v-61 we get;
[tex]y = \frac{82-Vj}{V-61}[/tex]
Therefore, the value of y is: [tex]y = \frac{82-Vj}{V-61}[/tex]